Pengimbuhan Vitamin-E dalam Ransum Kaya Asam Lemak Tidak Jenuh Terhadap Profil Darah Induk Domba Laktasi§ (VITAMIN-E SUPPLEMENTATION ON RICH POLY-UNSATURATED FATTY ACID RATION TO BLOOD PROFILE OF LACTATION EWES) - Fassah, Dilla Mareistia; Khotijah, Lilis (Jurnal Veteriner, 2016)
Sunflower oil is a source of rich poly-unsaturated fatty acid (PUFA) mainly Linoleic acid. PUFA on theewes ration was very useful due to its function as the precursors of prostaglandin. It plays an importantrole in the health and reproduction regulation. Early lactation was the critical period where the bodymetabolism is on an increasing stage. However, high level of PUFA on ewe’s lactation ration was also verysusceptible to induce lipid peroxidation which can cause health problems in the affected animals. Thesupplementation of vitamin E as antioxidant is needed to prevent the PUFA from oxidation damage. Theaim of this study was to evaluate the effect of vitamin E supplementation in the rich PUFA diet on theblood profile of lactating ewes. Fifteen ewes on lactation period were used in completely randomizednested design. The level of vitamin E supplementation was 30 IU, 60 IU and 90 IU then the blood profileevaluation was carried out on 28 and 56 days of lactation. The measured variables were haemoglobin,packed cell volume (PCV), erythrocytes, leukocytes, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC). The number of erythrocytesof ewes was 5.53-9.85 x 106/mm3, the MCV value was 32.19-46.20 fl and the MCH value was 10.91-17.27pg on day-28. The results showed that Vitamin E supplementation has significant effect on the number oferythrocytes (p<0,05), and the high significant effect on MCV as well as MCH values(P<0.01) of lactationewes blood. The Vitamin E supplementation until 90 IU was able to maintain the ewe’s blood profile onthe lactation periods.
Keywords: blood profile; lactation ewes; PUFA; vitamin-E